IMMATURE TO TOTAL NEUTROPHIL RATIO (I/T RATIO) ON NORMAL AND SEPSIS RISK NEONATUS FACTOR AT ULIN GENERAL HOSPITAL BANJARMASIN - Muhammad Rifky Ersadian Noor; F.X. Hendriyono; Ari Yunanto (Fakultas Kedokteran Universitas Lambung Mangkurat, 2017)
Abstract: Neonatal sepsis is the main cause of morbidity and mortality in neonates. Early diagnostic and appropriate treatment can reduce the mortality and morbidity rate. Immature neutrophil ratio tand total neutrophil (I/T ratio) can be used as one of early diagnostic tool of neonatal sepsis. The purpose of this research was to find difference of I/T ratio between normal neonates and neonates with sepsis risk factor at Ulin General Hospital Banjarmasin on April – June 2016. It was an analytic observational study and collected by accidental sampling. From 39 neonates, there was 23 normal neonates and 16 neonates with sepsis risk factor who diagnosed by competence pediatrics based on mayor and minor risk factor. Mean I/T ratio from normal neonates is 0,06 and neonates with sepsis risk factor is 0,16. From statistical test with independent T-test, there is significant difference p=0,000 (p<0,05). In conclusion, there is a difference of I/T Ratio between normal neonates and neonates with sepsis risk factor. Keywords: neonatal sepsis, I/T ratio, risk factor, neonates